Medicinal signaling cells: A potential antimicrobial drug store. Issue 11 (30th April 2020) - Hosseiniyan Khatibi, Seyed Mahdi; Kheyrolahzadeh, Keyvan; Barzegari, Abolfazl; Rahbar Saadat, Yalda; Zununi Vahed, Sepideh
Abstract: Medicinal signaling cells (MSCs) are multipotent cells derived from mammalian bone marrow and periosteum that can be extended in culture. They can keep their ability in vitro to form a variety of mesodermal phenotypes and tissues. Over recent years, there has been great attention over MSCs since they can impact the organ transplantation as well as autoimmune and bacterial diseases. MSCs can secrete different bioactive factors such as growth factors, antimicrobial peptides/proteins and cytokines that can suppress the immune system and prevent infection via direct and indirect mechanisms. Moreover, MSCs are able to increase bacterial clearance in sepsis models by producing antimicrobial peptides such as defensins, cathelicidins, lipocalin and hepcidin. It is the aim of the present review to focus on the antibacterial effector functions of MSCs and their mechanisms of action against the pathogenic microbes. Abstract : Medicinal signaling cells (MSCs) can secrete different bioactive factors such as growth factors, antimicrobial peptides/proteins and cytokines that can prevent infection via different mechanisms.